Rehabilitation of severely resorbed edentulous mandible using the modified visor osteotomy technique - Sverzut,Cassio Edvard (2009)
The prosthetic rehabilitation of an atrophic mandible is usually unsatisfactory due to the lack of support tissues, mainly bone and keratinized mucosa for treatment with osseointegrated implants or even conventional prosthesis. The prosthetic instability leads to social and functional limitations and chronic physical trauma decreasing the patient's quality of life. A 53-year-old female patient sought care at our surgical service complaining of impairment of her masticatory function associated with the instability of the lower total prosthetic denture. The clinical and complementary exams revealed edentulism in both arches, while the mandibular arch presented severe reabsorption resulting in denture instability and chronic trauma to the oral mucosa. The proposed treatment plan consisted in the mandibular rehabilitation with osseointegrated implants and fixed Brånemark's protocol prosthesis after mandibular reconstruction applying the modified visor osteotomy technique. The proposed technique offered predictable results for reconstruction of the severely resorbed edentulous mandible and posterior rehabilitation with osseointegrated implants.